The Influence of Employee Welfare, Work Environment and Work Motivation on Employee Performance - Ar Rosyd, M. Rizal; Ilham, Rachmad; Syamlan, Adiba Fuad (CV. Civiliza Publishing, 2025)
This study aims to analyze the influence of employee well-being, work environment, and work motivation on employee performance at PT. Indospring Tbk Plant 2 Gresik. The background of the research is based on the importance of human resource management as a key factor in enhancing the company's competitiveness. The research method used is a quantitative approach with purposive sampling technique involving 100 male employees. Data were collected through observation, literature study, and questionnaires using a Likert scale. Data analysis was conducted using multiple linear regression preceded by validity, reliability, and classical assumption tests. The results show that employee well-being, work environment, and work motivation have a significant partial and simultaneous effect on employee performance. The coefficient of determination (R²) value of 0.967 indicates that the three independent variables explain 96.7% of the dependent variable. Therefore, improving employee well-being, enhancing the work environment, and increasing work motivation can directly contribute to improving employee performance.